Processing of Woven Bamboo for the Economy of Village Communities - Danilo Carlo (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
The economic benefits of processing bamboo are examined in this thesis study. This paper examines the economic benefits of bamboo processing, including income generation, job creation, links to other economic sectors, and environmental benefits, as well as the operations involved in processing bamboo, such as harvesting, processing, weaving, and finishing. Lack of access to technology and markets, the cyclical nature of bamboo, and a lack of funding are just some of the difficulties that village groups who engage in bamboo processing encounter, and they are all explored in the research. The research concludes by outlining strategies for rural areas to maximize their financial gain from bamboo processing, such as expanding their product line, advertising their location as an eco-tourism destination, working together with designers and other interested parties, and educating and training their workforce. The research concludes that bamboo processing has the potential to become a sustainable economic activity for rural communities and offers suggestions for policy-makers, development organizations, and interested citizens.